TECHNOLOGY OF METAL PRESSURE WELDING - Khamdamov Sodik Talibjonivych (Web of Journals Publishing, 2024)
The technology of metal pressure welding has emerged as a significant advancement in the field of joining metals, offering enhanced mechanical properties and improved durability in welded structures. This article explores the fundamental principles of pressure welding processes, including methods such as friction welding, ultrasonic welding, and resistance welding. The advantages and limitations of each technique are discussed, along with their applications in various industries, including aerospace, automotive, and construction. The article also highlights recent innovations and research trends aimed at optimizing welding parameters and materials to achieve superior joint quality and efficiency. By examining case studies and experimental results, this work aims to provide a comprehensive overview of metal pressure welding technology, its operational principles, and its future prospects in modern manufacturing.
Keywords: Metal pressure welding, Friction welding, Ultrasonic welding, Resistance welding, Joint quality, Mechanical properties, Manufacturing technology, Welding parameters, Industrial applications, Innovations in welding.